Youth perspectives on sexually transmitted infections and sexual health in Northern Canada and implications for public health practice. Issue 1 (31st January 2016) - Healey, Gwen
Abstract : Objective: High rates of sexually transmitted infections in the Arctic have been a focus of recent research, and youth are believed to be at greatest risk of infection. Little research has focused on understanding youth perspectives on sexual health. The goal of this study was to collect the perspectives of youth in Nunavut on sexual health and relationships with the intent of informing public health practice. Method: This qualitative research study was conducted within an Indigenous knowledge framework with a focus on Inuit ways of knowing. Data were collected through face-to-face interviews in three Nunavut communities with 17 youth between the ages of 14 and 19 years. Participants were asked open-ended questions about their experiences talking about sexual health and relationships with their family, peers, teachers or others in the community. Results: There are four key findings, which are important for public health: (a) Parents/caregivers are the preferred source of knowledge about sexual health and relationships among youth respondents; (b) youth did not report using the Internet for sexual health information; (c) youth related sexual decision-making to the broader community context and determinants of health, such as poverty; and (d) youth discussed sexual health in terms of desire and love, which is an aspect of sexual health often omitted from the discourse. Implications and contribution: The youth in this study articulated perspectives on sexual health, which are largely neglected in current public health practice in the North. The findings from this study underscore the important role of community-led participatory research in contributing to our understanding of the public health challenges in our communities today, and provide direction for future interventions and research.